DETERMINAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN : STUDI PADA PERUSAHAAN MANUFAKTUR - Wildan Dwi Dermawan; Nanda, Ulfa Luthfia; Desiana, Desiana (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The establishment of the company, there is a negative impact, damage to nature. Theimpact of natural damage that has occurred has made the community demand thatthe company pay more attention to the damage. Corporate social responsibility orCSR is a form of balancing program between economic benefits and contributionsto the economy, society and the environment. Information on CSR activities is neededby the community to fulfill the right to feel safe, secure and prosperous. This studyaims to analyze the effect of the board of commissioners, gender diversity,profitability, leverage, company age on corporate social responsibility disclosure.The study population was all food and beverage sub-sector manufacturingcompanies listed on the Indonesia Stock Exchange during 2015-2017. This researchuses purposive sampling method. The results showed that gender diversity,profitability, leverage and company age did not have a significant effect oncorporate social responsibility disclosure, while the board of commisioners variables had a significant effect on corporate social responsibility disclosure. Thisresearch is expected to be an additional reference for accounting research,especially those related to corporate social responsibility disclosure. In addition,this research is expected to become a reference for companies in disclosingcorporate social responsibility.